Aktivitas Penangkapan Radikal Bebas dari Infus Kelopak Bunga Rosella yang Difermentasi dengan Lactobacillus - Sartini, .; Lethe, Christiana; Frengky, . (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
The research aimed to investigate the free radical scavenging activity of ethyl acetate fraction of roselle calyces infusion fermented by Lactobacillus casei strain Shirota against free radical agent, DPPH (2,2-di-phenyl-2-picrylhydrazyl). In sequence, the roselle calyces were extracted by infusion method with concentration at 5% w/v. The infusion was fermented using Lactobacillus casei strain Shirota during 3x24 hours at 37⁰C. As regard the fermentation process, the result of that was extracted using ethyl acetate. Free radical scavenging activity was measured using DPPH method with unfermented-ethyl acetate fraction as control negative. As the result, both fermented and unfermented-ethyl acetate fraction exhibited free radical scavenging activity at 370.68 ppm and 685.49 ppm, respectively. These results suggest that antioxidant activity of fermented-ethyl acetate fraction could be 1.85 greater than unfermented-ethyl acetate fraction of roselle calyces infusionKeywords : Hibiscus sabdariffa L., Lactobacillus casei Shirota strain, free radical scavenging, DPPH